2017
DOI: 10.1186/s40623-017-0645-z
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic ground motion simulation of the 2016 Meinong, Taiwan earthquake

Abstract: We applied a stochastic method for the finite-fault modeling of strong ground motions to the 2016 Meinong, Taiwan earthquake. Newly developed attenuation models in Southern Taiwan with the frequency-dependent Q = 86.4f 0.73 and the high-frequency decay factor κ 0 were used in the synthetic model. The horizontal-to-vertical spectral ratios (HVSR) were calculated from weak motions and the Meinong mainshock and used for the site amplification correction of the synthetic waveforms produced by the stochastic ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Chen et al (2019) obtained a strong-motion generation area (SMGA) model of the 2016 Meinong event on the NS-striking fault plane. However, most relevant studies (e.g., Huang et al 2016;Lee et al 2016;Chen et al 2017;Kanamori et al 2017;Diao et al 2018a, b;Lin et al 2018;Chen, 2019) have suggested an EW-striking rupture. We also considered the EW-striking fault plane for the 2016 Meinong event.…”
Section: Broadband Strong-motion Simulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al (2019) obtained a strong-motion generation area (SMGA) model of the 2016 Meinong event on the NS-striking fault plane. However, most relevant studies (e.g., Huang et al 2016;Lee et al 2016;Chen et al 2017;Kanamori et al 2017;Diao et al 2018a, b;Lin et al 2018;Chen, 2019) have suggested an EW-striking rupture. We also considered the EW-striking fault plane for the 2016 Meinong event.…”
Section: Broadband Strong-motion Simulationmentioning
confidence: 99%
“…Moreover, it could be noticed that the liquefactions also occurred within the high PGV region for both the 2010 Jiashian and 2016 Meinong events. Boore et al (1989) indicated that PGA could be reduced through deamplification by the nonlinear soil effect, and Chen et al (2017) demonstrated that the liquefactions caused by the 2016 Meinong event were located in a region with a significant reduction in PGA. Several studies have suggested that the relatively low-velocity region is beneath the significant coseismic uplift region of the 2016 Meinong event, which could be controlled by the high pore fluid pressure within (See figure on next page.)…”
Section: Localized High Pgv Attributed To Soft-sediment Amplificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Ren et al (2017) quantify the amount of soil nonlinearity by using various indices based on the horizontal-to-vertical spectral ratio applied to strong ground motion records obtained during and after the 2008 Wenchuan earthquake, China (Ms8.0), and investigate their correlation with loading or site parameters. Similarly, Chen et al (2017) analyze the amount of nonlinear site response in the (estimated) strong shaking area in relation to the loading and site parameters for the 2016 Meinong earthquake and propose a method to incorporate the resulting nonlinear frequency shifts in otherwise linear stochastic ground motion simulations. Lu et al (2017) investigate the degree of damage to low-rise buildings as a result of soil liquefaction in the superficial layer during the 2016 Meinong earthquake, Taiwan, and emphasize some nonconservative limitations of existing methods, linked to poor accounting of the underlying site conditions.…”
mentioning
confidence: 99%